Volumetric Analysis of Sphenoid Sinus in Patients with Symptomatic Nasal Septal Deviation: A Cross-sectional Study - Sheetal Rai; Rahul Kunnath; Adarsh Kibballi Madhukeshwar (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Nasal Septal Deviation (NSD) is known to influence the anatomy of the paraseptal structures, such as the lateral nasal wall and middle turbinate, thereby causing changes in ethmoid cell volume and maxillary sinus. However, there is not much literature on the influence of NSD on sphenoid sinus volume. Aim: To evaluate the effect of NSD on the volume of sphenoid sinus. Materials and Methods: A cross-sectional study was conducted over a period of one year at a tertiary care hospital in Karnataka, India on 45 patients with symptomatic NSD. Diagnostic Nasal Endoscopy (DNE) and Computed Tomography (CT) scans of the nose and Paranasal Sinuses (PNS) were performed on all patients. NSD was classified into three types based on the degree of septal deviation on CT scan. Sphenoid sinus volumes were measured, and the relationship between NSD and sphenoid sinus volume was analysed using OSIRIX software on the MAC system. Statistical analysis was done using the Wilcoxon signed-rank test and the Kruskal-Wallis test. Results: The mean age of the patients included in the study was 30.89±10.19 years. The male-to-female ratio was 2.75:1. The majority of the patients had NSD to the right (57%). NSD was found to be 1.3 times more frequent on the right-side compared to the left. The angle of NSD ranged between 2.10° and 18°. The majority of the patients were in group I (n=35), while group II and III had seven and three patients, respectively. The total ipsilateral volume was found to be 7.43±3.46 cm3 and the contralateral volume was 7.98±4.19 cm3. There was no statistically significant difference between ipsilateral and contralateral sphenoid sinus volumes in the population (p-value=0.781). When each group was compared, no significant difference between the total sphenoid cell volumes on the ipsilateral (p-value=0.557) and contralateral (p-value=0.405) sides of the NSD was seen. Conclusion: NSD does not affect the volume of the sphenoid sinus, irrespective of the degree of septal deviation.